2018
DOI: 10.1111/isj.12222
|View full text |Cite
|
Sign up to set email alerts
|

Flamingos on a slackline: Companies' challenges of balancing the competing demands of handling customer information and privacy

Abstract: Providers of online services are under increasing pressure to leverage the value inherent in customer data to remain competitive. At the same time, however, Internet users' privacy has become more and more subject to public debate, and companies must protect this privacy if they want to attract and retain customers. It seems that companies struggle to satisfy these competing demands, and neglecting either could have detrimental effects on their success. Different streams of research underline the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…websites) become more adept at collecting and sharing information, often without sufficiently accommodating personal security needs and obligations (Adorjan and Ricciardelli, 2019). Specifically, research investigating consumers' vulnerability and how banks determine optimal disclosure levels when managing sensitive information is limited (Gerlach et al , 2019). Furthermore, a research gap also exists concerning how much of the risk associated with data disclosure is perceived or actual (Wu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…websites) become more adept at collecting and sharing information, often without sufficiently accommodating personal security needs and obligations (Adorjan and Ricciardelli, 2019). Specifically, research investigating consumers' vulnerability and how banks determine optimal disclosure levels when managing sensitive information is limited (Gerlach et al , 2019). Furthermore, a research gap also exists concerning how much of the risk associated with data disclosure is perceived or actual (Wu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Organizations face challenges in balancing the need to leverage consumer data with potential negative consequences of perceived disregard for consumers' privacy (Gerlach et al, 2019). Indeed, privacy research has long grappled with recommendations around finding the ideal balance of transparency (Gerlach et al, 2019) and communicating with consumers in ways that inform them of privacy practices without raising concern (Karwatzki et al, 2017). We provide further support for studies advocating visualized privacy policies (e.g.…”
Section: Enhancing Perceptions Of Privacy and Trustmentioning
confidence: 62%
“…Our study also offers important insights from a practical perspective and answers calls for research on effective privacy policy visualization (Soumelidou and Tsohou, 2019) and privacy policy research in the E-commerce context (Libaque-S aenz et al, 2021). Organizations face challenges in balancing the need to leverage consumer data with potential negative consequences of perceived disregard for consumers' privacy (Gerlach et al, 2019). Indeed, privacy research has long grappled with recommendations around finding the ideal balance of transparency (Gerlach et al, 2019) and communicating with consumers in ways that inform them of privacy practices without raising concern (Karwatzki et al, 2017).…”
Section: Enhancing Perceptions Of Privacy and Trustmentioning
confidence: 99%
“…For example, in 2017, Equifax announced that more than 145 million customers' sensitive information had been stolen, resulting in 240 consumer lawsuits resulting in nearly $90 million in default-related costs [10,11]. Previous studies have shown that data leakage can reduce the market value of enterprises, cause large fluctuations in the stock market [12], and even affect the behaviors of competitors in the market [13].…”
Section: Introductionmentioning
confidence: 99%